2011
DOI: 10.4161/cbt.12.12.18671
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine fuels a vicious cycle of autophagy in the tumor stroma and oxidative mitochondrial metabolism in epithelial cancer cells

Abstract: Glutamine metabolism is crucial for cancer cell growth via the generation of intermediate molecules in the tricarboxylic acid (TCA) cycle, antioxidants and ammonia. The goal of the current study was to evaluate the effects of glutamine on metabolism in the breast cancer tumor microenvironment, with a focus on autophagy and cell death in both epithelial and stromal compartments. For this purpose, MCF7 breast cancer cells were cultured alone or co-cultured with nontransformed fibroblasts in media containing high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 42 publications
(56 reference statements)
2
122
0
Order By: Relevance
“…Based on the positive correlations between tumoral GLS1-stromal GLS1 (rZ0.191, P!0.001), tumoral GDHstromal GDH (rZ0.106, PZ0.005), and tumoral ASCT2-stromal ASCT2 expression (rZ0.302, P!0.001), we identified a relationship between tumoral and stromal glutamine metabolism. Previous studies have reported that the byproducts of glutaminolysis in cancer cells, such as ammonia, diffuse into the stroma and stimulate autophagy and glutamine synthesis in cancer-associated fibroblasts, which subsequently feeds cancer cells in a vicious cycle (Eng & Abraham 2010, Marino & Kroemer 2010, Pavlides et al 2010, Ko et al 2011, MartinezOutschoorn et al 2011. One previous study utilized co-culturing of MCF-7 breast cancer cells (luminal A type) with fibroblasts and found increased expression of GLS, GDH, and SLC6A14 (glutamine importer) and reduced glutamine neosynthesis when compared with breast cancer single-cell culture without fibroblast, thus demonstrating stroma-tumor glutamine transportation (Ko et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the positive correlations between tumoral GLS1-stromal GLS1 (rZ0.191, P!0.001), tumoral GDHstromal GDH (rZ0.106, PZ0.005), and tumoral ASCT2-stromal ASCT2 expression (rZ0.302, P!0.001), we identified a relationship between tumoral and stromal glutamine metabolism. Previous studies have reported that the byproducts of glutaminolysis in cancer cells, such as ammonia, diffuse into the stroma and stimulate autophagy and glutamine synthesis in cancer-associated fibroblasts, which subsequently feeds cancer cells in a vicious cycle (Eng & Abraham 2010, Marino & Kroemer 2010, Pavlides et al 2010, Ko et al 2011, MartinezOutschoorn et al 2011. One previous study utilized co-culturing of MCF-7 breast cancer cells (luminal A type) with fibroblasts and found increased expression of GLS, GDH, and SLC6A14 (glutamine importer) and reduced glutamine neosynthesis when compared with breast cancer single-cell culture without fibroblast, thus demonstrating stroma-tumor glutamine transportation (Ko et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In deed, re cent work sup ports the hy poth e sis that can cer as so ci ated fi brob lasts (CAFs) un dergo a cata bolic shift to sup ply tu mor cells with ke tone bod ies and glu t a mine [79]. For in stance, Ko et al [80] showed that au tophagy in creased in fi brob lasts grown in the pres ence of MCF7 breast can cer cells. Glu t a mine se creted by au tophagic fi brob lasts in turn fu eled the mi to chon dr ial ac tiv ity of MCF7 can cer cells [79,80].…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%
“…For in stance, Ko et al [80] showed that au tophagy in creased in fi brob lasts grown in the pres ence of MCF7 breast can cer cells. Glu t a mine se creted by au tophagic fi brob lasts in turn fu eled the mi to chon dr ial ac tiv ity of MCF7 can cer cells [79,80]. An other study showed that prostate can cer cells can redi rect the me tab o lism of ad ja cent fi brob lasts to wards a gly colytic phe no type.…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%
“…25 Thus, we explored the possibility that ethanol exposure protects MCF7 cells against autophagy. Figure 3D shows that ethanol treatment decreases the expression of several key autophagy markers, namely BNIP3, LC3, Cathepsin B and, to a lesser extent, Lamp-1, suggesting that ethanol promotes autophagy resistance in epithelial cancer cells.…”
Section: Resultsmentioning
confidence: 99%